REPOSITIONING STASIUN TELEVISI LOKAL DALAM MEMBANGUN IMAGE SEBAGAI TV INFORMASI - Lukmiyati, Sri (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
The television industry in Indonesia is growing fast, nowaday, there are more than 200 tv stations. Regarding that, each station must has a good and clear positioning to win the competition. However, the positioning process can not always going well, some of them had positioning gap, which is caused by many factors. This research took Jak tv, one of the local tv station in Jakarta. There were too many various information for the audiences, e.g one of the health information had made misperception of Jak tv image for the audience. Then the repositioning was made to build image of Jak tv as the information television. This research using a qualitative approach and a post-positivism paradigm. The researcher did an in-depth interview, participatory observation and documents study. This is an evaluation research to analyse the repositioning strategi of Jak tv which had confused positioning to build image as the information television. The result showed that Jak tv had made some repositioning strategies include readjustment of the STP (segmentation, targeting, positioning), the managerial transformation of the human resources, renew the broadcasting equipments and technologies, and change over of the on air look and the content of broadcast programs. Jak tv always share with the audience and the advertiser of the new positioning by using media promotion both on air and off air.